2014
DOI: 10.3747/co.21.1914
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Renal Cell Carcinoma without Evidence of a Primary Renal Tumour

Abstract: new cases of rcc and 13,500 deaths every year are attributed to this type of renal cancer 1 . In recent decades, the incidence of rcc has been increasing, and the average tumour size at diagnosis has been declining 2 . Those trends are partially attributable to the widespread use of noninvasive abdominal imaging modalities, which have allowed for more incidental findings of asymptomatic tumours. Renal cell carcinoma is about 50% more common in men than in women, and it is unusual in patients under 40 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Seven patients had surgery to treat a solitary metastatic lesion, with no additional systemic treatment provided. 8,9,11,[15][16][17] Eleven patients described in 8 case reports received targeted therapies with sunitinib (n ¼ 6), 6,7,10,18,19 pazopanib (n ¼ 2), 14,19 temsirolimus (n ¼ 2), 12 and everolimus (n ¼ 1). 13 Efficacy data showed that 8 (72%) of 11 patients responded to treatment, and 9 (82%) of 11 were alive when the cases were reported, surviving between 6 weeks and 36 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven patients had surgery to treat a solitary metastatic lesion, with no additional systemic treatment provided. 8,9,11,[15][16][17] Eleven patients described in 8 case reports received targeted therapies with sunitinib (n ¼ 6), 6,7,10,18,19 pazopanib (n ¼ 2), 14,19 temsirolimus (n ¼ 2), 12 and everolimus (n ¼ 1). 13 Efficacy data showed that 8 (72%) of 11 patients responded to treatment, and 9 (82%) of 11 were alive when the cases were reported, surviving between 6 weeks and 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…This entity has only rarely been described in the literature. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Renal-cell carcinoma (RCC) is a group of cancers arising from the nephron, where 70% of RCC are clear-cell RCC. Because of mutation in the Von Hippel-Lindau gene, a high amount of vascular endothelial growth factor (VEGF) is produced, resulting in increased angiogenesis, cell growth, metabolism, and immunesuppression.…”
Section: Introductionmentioning
confidence: 99%
“…It still remains unclear how mRCC occurs with an unidentifiable primary lesion; however, there have been several possible explanations [5,6]. The mass could be occult, hence undetectable by imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, presenting with mRCC with an undetectable primary is infrequent. A total of 12 cases were documented based on our literature review [5][6][7][8][9][10][11][12]; none of which had diffuse lymphadenopathy metastasizing from an unidentifiable renal primary as presented in our case. In such a challenging situation, immunohistochemical profiling as well as the promising field of molecular genetics aid in reaching a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation